SELECTIVE RELEASE OF CONTENT FROM MICROSOMAL VESICLES WITHOUT MEMBRANE DISASSEMBLY : I. Permeability Changes Induced by Low Detergent Concentrations - Kreibich, Gert (The Rockefeller University Press, 1973)
Rat liver rough microsomes treated with a series of desoxycholate (DOC) concentrations from 0.003 to 0.4% were analyzed by isopycnic sucrose density gradient centrifugation in media containing high or low salt concentrations. Tritium-labeled precursors administered in vivo were used as markers for ribosomes (orotic acid, 40 h), phospholipids (choline, 4 h), membrane proteins (leucine, 3 days), and completed secretory proteins of the vesicular cavity (leucine, 30 min). Within a narrow range of DOC concentrations (0.025–0.05%), the vesicular polypeptides were selectively released from the microsomes, while ribosomes, nascent polypeptides, and microsomal enzymes of the electron transport systems were unaffected. The detergent concentration which led to leakage of content was a function of the ionic strength and of the microsome concentration. At the lowest effective DOC concentration the microsomal membranes became reversibly permeable to macromoles as shown by changes in the density of the vesicles in Dextran gradients and by the extent of proteolysis by added proteases. Incubation of rough microsomes with proteases in the presence of 0.025% DOC also led to digestion of proteins from both faces of the microsomal membranes and to a lighter isopycnic density of the membrane vesicles.